2014
DOI: 10.1186/1471-2407-14-214
|View full text |Cite
|
Sign up to set email alerts
|

Loss of MTUS1/ATIP expression is associated with adverse outcome in advanced bladder carcinomas: data from a retrospective study

Abstract: BackgroundSeventy percent of all bladder tumours tend to recur and need intensive surveillance, and a subset of tumours progress to muscle-invasive and metastatic disease. However, it is still difficult to find the adequate treatment for every individual patient as it is a very heterogeneous disease and reliable biomarkers are still missing. In our study we searched for new target genes in the critical chromosomal region 8p and investigated the potential tumour suppressor gene candidate MTUS1/ATIP in bladder c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…Some candidate oncogenes and tumor suppressors have been identified among these amplified and deleted loci and have characterized using this approach. For example, the MTUS1 and SFRP1 genes on chromosome 8p22 and 8p12-11.1 loci have been identified for their tumor suppression function in UBUC [ 17 , 18 ]. Regarding chromosome 8q, our results are consistent with those of previous studies which have reported gains involving chromosome 8q as one of the most common events in UBUC.…”
Section: Discussionmentioning
confidence: 99%
“…Some candidate oncogenes and tumor suppressors have been identified among these amplified and deleted loci and have characterized using this approach. For example, the MTUS1 and SFRP1 genes on chromosome 8p22 and 8p12-11.1 loci have been identified for their tumor suppression function in UBUC [ 17 , 18 ]. Regarding chromosome 8q, our results are consistent with those of previous studies which have reported gains involving chromosome 8q as one of the most common events in UBUC.…”
Section: Discussionmentioning
confidence: 99%
“…MTUS1 is localized at chromosome 8p22 and comprises 17 exons 47 . Downregulation or loss of MTUS1 is a frequent event and indicator of poor survival in bladder carcinomas, lung cancer, salivary adenoid cystic carcinoma, gastric cancer, and breast cancer [48][49][50][51][52] . In addition, depletion of MTUS1 increases microtubule dynamics and contributes to metastasis in breast cancer 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, GBC remains aggressive, needing new biomarkers. MTUS1 is a tumor-suppressor gene as was shown in several studies (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). Thus, the expression of MTUS1 protein and mRNA in tumor tissues was significantly lower than that in normal tissues of several human tumor types, including breast cancer, gastric carcinoma, head and neck squamous cell carcinoma, salivary adenoid cystic carcinoma, and urinary bladder cancer (8,11,13,16,17).…”
Section: Kaplan-meier Analysis For Cancer-specific (A) and Disease-mentioning
confidence: 88%
“…Thus, the expression of MTUS1 protein and mRNA in tumor tissues was significantly lower than that in normal tissues of several human tumor types, including breast cancer, gastric carcinoma, head and neck squamous cell carcinoma, salivary adenoid cystic carcinoma, and urinary bladder cancer (8,11,13,16,17). In bladder carcinoma, the expression of MTUS1 protein was reduced in papillary and advanced bladder carcinomas (7). Low expression of MTUS1 was correlated with adverse clinical outcome.…”
Section: Kaplan-meier Analysis For Cancer-specific (A) and Disease-mentioning
confidence: 96%